Diagnosis of holoprosencephaly in the first trimester - Paliwal, Shweta; Singh, Chanchal; Gholkar, Nikhil; Kaul, Anita (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2016)
We present a case of alobar holoprosencephaly diagnosed antenatally at 12 weeks gestation. Early diagnosis of such lethal malformation is important so that the parents have an option for termination at an early gestational age minimizing maternal morbidity and social impact on the family.